Waking Yourself Up: The Liberatory Potential of Critical University Studies - Arthur, Mikaila Mariel Lemonik; Renshaw, Scott Leo (Radical Teacher, 2017)
Critical university studies courses can provide students with a context in which to learn not only about the concealed workings and hidden curriculum of the university, but more than that a liberatory space in which to find voice in shaping their own futures. This paper explores the liberatory potential of critical university studies through a conversation between a faculty member who designed and taught an interdisciplinary general education course on higher education and a student who was enrolled in the course the first time it was offered. The conversation explores the course’s pedagogy as both professor and student contemplate the ways in which contemporary higher education may limit the horizons of first-generation students and the ways in which critical university studies can open up possibilities and provide students with a sense of self-efficacy.